Probiotics and the development of very low birthweight infants: follow-up study of a randomised trial - Satoshi Kusuda; Satsuki Totsu; Masaki Terahara; Takeo Kasai; Hirokazu Arai; Maki Sato; Niro Ujiie; Tsutomu Kawahara; Tsutomu Isii; Junichi Arai; Atsushi Baba; Kinuko Kojima; et al. (BMJ Publishing Group, 2018)
Abstract Objective To investigate the effect of Bifidobacterium bifidum OLB6378 on the development of very low birthweight (VLBW) infants at 18 months of corrected age.Design Long-term follow-up study of a cluster-randomised, placebo-controlled trial.Patients VLBW infants (birth weight <1500 g) born between January 2010 and March 2011 and managed at 19 neonatal intensive care unit facilities assigned to two groups to account for the effect of probiotic cross-contamination within facilities.Interventions For VLBW infants, administration of OLB6378 as a probiotic was started within 48 hours of birth and continued until the body weight reached 2000 g.Main outcome measures At 18 months of corrected age, physical status and developmental quotient (DQ18) were assessed. The distribution of DQ18 scores was categorised into four levels of development: <70, significant developmental delay; 70-84, moderate developmental delay; 85-99, without developmental delay; ≥100, average development or better.Results Among 153 infants assigned to the OLB6378 administration group and 130 assigned to the placebo administration group, 102 and 105 infants, respectively, underwent the 18-month medical examination. The distribution of developmental levels (DQ18 scores <70, 70-84, 85-99 and ≥100) was significantly more favourable for OLB6378 administration (12, 12, 25 and 40 infants, respectively) than for placebo administration (15, 17, 23 and 24 infants, respectively) (ordered logistic regression analysis: partial correlation coefficient, 0.589; P value, 0.038).Conclusions Although limited by assessment rates, result suggests that OLB6378 may have a beneficial effect on the psychological development in VLBW infants.Clinical trial registration UMIN000002543.